Prevention of sexual transmission of Ebola in Liberia through a national semen testing and counselling programme for survivors: an analysis of Ebola virus RNA results and behavioural data. Issue 10 (October 2016) - Soka, Moses J; Choi, Mary J; Baller, April; White, Stephen; Rogers, Emerson; Purpura, Lawrence J; Mahmoud, Nuha; Wasunna, Christine; Massaquoi, Moses; Abad, Neetu; Kollie, Jomah; Dweh, Straker; et al.
Summary: Background: Ebola virus has been detected in semen of Ebola virus disease survivors after recovery. Liberia's Men's Health Screening Program (MHSP) offers Ebola virus disease survivors semen testing for Ebola virus. We present preliminary results and behavioural outcomes from the first national semen testing programme for Ebola virus. Methods: The MHSP operates out of three locations in Liberia: Redemption Hospital in Montserrado County, Phebe Hospital in Bong County, and Tellewoyan Hospital in Lofa County. Men aged 15 years and older who had an Ebola treatment unit discharge certificate are eligible for inclusion. Participants' semen samples were tested for Ebola virus RNA by real-time RT-PCR and participants received counselling on safe sexual practices. Participants graduated after receiving two consecutive negative semen tests. Counsellors collected information on sociodemographics and sexual behaviours using questionnaires administered at enrolment, follow up, and graduation visits. Because the programme is ongoing, data analysis was restricted to data obtained from July 7, 2015, to May 6, 2016. Findings: As of May 6, 2016, 466 Ebola virus disease survivors had enrolled in the programme; real-time RT-PCR results were available from 429 participants. 38 participants (9%) produced at least one semen specimen that tested positive for Ebola virus RNA. Of these, 24 (63%) provided semen specimens that tested positive 12 months or longer after Ebola virus disease recovery. The longest interval between discharge from an Ebola treatment unit and collection of a positive semen sample was 565 days. Among participants who enrolled and provided specimens more than 90 days since their Ebola treatment unit discharge, men older than 40 years were more likely to have a semen sample test positive than were men aged 40 years or younger (p=0·0004). 84 (74%) of 113 participants who reported not using a condom at enrolment reported using condoms at their first follow-up visit (p<0·0001). 176 (46%) of 385 participants who reported being sexually active at enrolment reported abstinence at their follow-up visit (p<0·0001). Interpretation: Duration of detection of Ebola virus RNA by real-time RT-PCR varies by individual and might be associated with age. By combining behavioural counselling and laboratory testing, the Men's Health Screening Program helps male Ebola virus disease survivors understand their individual risk and take appropriate measures to protect their sexual partners. Funding: World Health Organization and the US Centers for Disease Control and Prevention.